Penanaman Modal Asing dan Penyerapan Tenaga Kerja di Provinsi Jawa Barat - Astuti, Riska Dwi; Gunawan, Gugun (Jurusan Ilmu Ekonomi, Fakultas Bisnis dan Ekonomika, Universitas Islam Indonesia, 2023)
Purpose – This research aims to analyze the influence of foreign direct investment (FDI) on labor absorption in West Java Province. Methods – Panel data from districts/cities in West Java in the 2017-2021 period were obtained from the Central Statistics Agency. Panel data regression analysis was carried out using the fixed effects method. Findings – The results of the analysis show that FDI has no effect on labor absorption in the West Java. In this research, it was found that labor absorption was influenced by education variables and gross regional income (GRDP) variables. Implication – The impact of FDI on labor absorption cannot be overstated. However, there is a possibility that it will take a long time for foreign investment to have an effect on labor absorption. Originality – Research on foreign investment in the province with the highest level of FDI in Indonesia on employment is still very rare to find. Moreover, this research utilizes panel data which statistically has advantages compared to cross-section or time series data alone.